Molecular mechanisms of synaptogenesis - Qi, Cai; Luo, Li-Da; Feng, Irena; Ma, Shaojie (Frontiers in Synaptic Neuroscience, 2022)
Synapses are the basic units for information processing and storage in the nervous system. It is only when the synaptic connection is established, that it becomes meaningful to discuss the structure and function of a circuit. In humans, our unparalleled cognitive abilities are correlated with an increase in the number of synapses. Additionally, genes involved in synaptogenesis are also frequently associated with neurological or psychiatric disorders, suggesting a relationship between synaptogenesis and brain physiology and pathology. Thus, understanding the molecular mechanisms of synaptogenesis is the key to the mystery of circuit assembly and neural computation. Furthermore, it would provide therapeutic insights for the treatment of neurological and psychiatric disorders. Multiple molecular events must be precisely coordinated to generate a synapse. To understand the molecular mechanisms underlying synaptogenesis, we need to know the molecular components of synapses, how these molecular components are held together, and how the molecular networks are refined in response to neural activity to generate new synapses. Thanks to the intensive investigations in this field, our understanding of the process of synaptogenesis has progressed significantly. Here, we will review the molecular mechanisms of synaptogenesis by going over the studies on the identification of molecular components in synapses and their functions in synaptogenesis, how cell adhesion molecules connect these synaptic molecules together, and how neural activity mobilizes these molecules to generate new synapses. Finally, we will summarize the human-specific regulatory mechanisms in synaptogenesis and results from human genetics studies on synaptogenesis and brain disorders.